Perancangan Program Aplikasi Kriptosistem Menggunakan Algoritma Square Yang Dimodifikasi Dan Fungsi Hash Sha-1 - Silalahi, Marzuki; P., Tumpal; Susanti, Herlina (Lembaga Penerbitan Universitas Esa Unggul, 2006)
Security and confidentiality of data or information has become an important issue within each person or in an organization. Especially, if this concerned dataÃ‚Â is in a computer connected with public network, such as LAN. The data will be vulnerable of computer crime done by unauthorized person. This article will discussed about designing a cryptographic application by using a combination between symmetric algorithm SQUARE and hash function SHA-1, to provide not only security but also authenticity in message delivery through network. Symmetric algorithm SQUARE with 128 bits key length will provide security of message delivery through network, by encrypting the message into an incomprehensible form, so it can not be accessed by unauthorized person, only by the one who also knowsÃ‚Â the key. While using a hash algorithm SHA-1 (Secure Hash Algorithm), user can produce message digest and use it as a digital signature of the message which provide authenticity, by then user will know if the message is really come from a trusted person.Keywords: Cryptosystem, SQUARE, SHA-1, Message Authentication, Conventional Encryption, Computer Security, Digital Signature, Hash Algorithm, Symmetric-Key Algorithm, Public-Key Encryption.